Inclusive Education Between Humanistic Idea and Corporative Model of Education: Are the Special Schools Better? - Cerić, Haris; Amel Alić (European Journal of Multidisciplinary Studies, 2020)
In this paper a paradox of global educational politics is problematized (GERM – global education movement) that is reflected in education reforms of numerous countries as it is insisted on uncompromizing introduction of inclusive education, while at the same time, more and more bigger breakthrough of neoliberalism is evident in education. Neoliberal education, that is corporative model of education, based on marketing orientation and imposing the demands for higher academic standards in order schools to be more competitive, is contradictory to humanistic and egalitarian idea of inclusion in education with the final aim of improvement of inclusive education in which all children, young and adults no matter of differencies, are given an opportunity to take part in and to give their own contribution. In practice, it is also questioned the co-existence of inclusive education and corporative model of education along with presenting the reflections and researches of some authors who emphazise the advantages of special education.